The Relationship Between Testosterone Hormone On Some Bio – kinematical Indicators Of Snatch During weightlifters Preparation Phase - Ahmed, Ali; Raad, Ahmed (Journal of Physical Education, 2018)
The Relationship Between Testosterone Hormone On Some Bio – kinematical Indicators Of Snatch During weightlifters Preparation PhaseThe importance of the research lies in identifying the relationship between testosterone hormone and some bio – kinematical indicators (ability, work, motor energy) during weightlifters' special perpetration phase. The aim of the test is to give a clear picture about the weightlifter to the trainer's about physical readiness (internal) and motor readiness (external) preparation period. Thus, the research society was the young quartiles in the AL_Gaesh alreade Club and their number was (5) and they were (0.62) of the original society (8). The researcher measured the variables at the beginning of the preparation period of 8/4/2017 and the hall of the Faculty of Physical Education and Sciences at 10:30 a.m.  In the presence of the work team (field) as the researcher photographed the samples in the performance of the regular doses also drew blood to measure the hormones in the laboratory of the University of Baghdad, and the results indicated no significant correlation between testosterone and biochemical parameters used in the research.